2009
DOI: 10.1080/11250000802484869
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and ultrastructure of the gills in two Urodela species:Salamandrina terdigitataandTriturus carnifex

Abstract: Gill morphology and ultrastructure are described for Triturus carnifex and Salamandrina terdigitata with emphasis on differences occurring between two species that inhabit different aquatic biotopes. The morphology and ultrastructure have been studied using light microscopy and both scanning and transmission electron microscopy. The general organization of the gills is similar in the two species and shows the characteristics of Urodela larvae in which the gills consist of three tufts of filaments supported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…36 The importance of the gill apparatus in terms of respiration has been discussed by some scholars. 37 However, there are a few studies on the external gills of tadpoles with regard to the effects of low pH. 24,38 In fact, no recent reports are available in the existing literature on the effects of low and high pH on the external gills of anuran tadpoles, except our recent findings.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…36 The importance of the gill apparatus in terms of respiration has been discussed by some scholars. 37 However, there are a few studies on the external gills of tadpoles with regard to the effects of low pH. 24,38 In fact, no recent reports are available in the existing literature on the effects of low and high pH on the external gills of anuran tadpoles, except our recent findings.…”
Section: Discussionmentioning
confidence: 70%
“…32 The latest finding suggested that amphibian gills play a crucial role in oxygen uptake and osmoregulation. 37 However, it has been suggested that gill damage in amphibian larvae may not be the sole cause of death among the larvae, as oxygen uptake is not merely restricted to the gills; it is also absorbed through the skin. 49 It should be noted that the comparative morphology of the external gills of some species of anurans has received less attention possibly due to the fact that they do not last long.…”
Section: Discussionmentioning
confidence: 99%
“…A and B). This general epithelial organization is typical of anuran external gills (Brunelli et al., ) and the gill filaments of teleost fish (Laurent and Dunel, ’80), and facilitates gas exchange from the environment to the blood. Likewise, the external gills of juvenile African lungfish Protopterus dolloi also show blood vessels separated from the external environment by only one or two cell layers (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The epithelial surface of anuran external gills when visualized with scanning electron microscopy (SEM) is characterized by the presence of three cellular types: polyhedric pavimentous cells equipped with microridges, cells rich in microvilli, and ciliated cells (Brunelli et al., ). Here, we have imaged the epithelium of PFFs from specimens collected in the dry and rainy seasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation